Phosphorus Sources Combined with Doses of Organic Compost Increased the Population of Soil Microorganisms and P Level in the Soil and Plant and the Dry Matter of Sugarcane - Caione, Gustavo; de Mello Prado, Renato [UNESP]; de Lima Vasconcelos, Ricardo [UNESP]; de Souza Junior, Jonas Pereira [UNESP]; Campos, Cid Naudi Silva [UNESP]; Moda, Leandro Rosatto [UNESP]; Castellanos González, Leonides [UNESP] (Springer Nature, 2020)
The aim of the study was to evaluate the effect of P sources and filter cake, enriched or not with biofertilizers and liquid peat, on the microbial population and the soil available P levels and shoot dry matter and P accumulation by sugarcane. The experiment was conducted in a greenhouse in a completely randomized design with factorial arrangement 4 × 3 + 1 and three replications. The treatments consisted in four sources of P: simple superphosphate, triple superphosphate, monoammonium phosphate and reactive natural phosphate combined with three levels of organic compound: without filter cake, decomposed filter cake (30 t ha−1, dry basis) and decomposed filter cake enriched with liquid peat (4 mL kg−1 of filter cake) and biofertilizers (480 mL kg−1 of filter cake) and a control treatment without organic compound and without phosphorus. At 45 and 110 days after planting the total population of bacteria and fungi, phosphate-solubilizing microorganisms and total microorganisms were evaluated. After 60 and 110 days, the soil available P, plants’ P and dry matter and P accumulation were evaluated. The organic compound increased the population of soil microorganism, the soil P levels, the accumulation of P and dry matter by the plants, regardless of the source of P, although the enrichment with biofertilizer and liquid peat did not enhance this effect. In conclusion, the presence of organic compost enhances the effects of phosphate fertilization.
Keywords: Microorganisms; Organic compound; Saccharum spp; Soil biology